2021
DOI: 10.21203/rs.3.rs-309377/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An external validation of the Candiolo nomogram in a cohort of prostate cancer patients treated by external-beam radiotherapy

Abstract: Backgroundthe aim of this study is to perform an external validation for the Candiolo nomogram, a predictive algorithm of biochemical and clinical recurrences in prostate cancer patients treated by radical Radiotherapy, published in 2016 on the journal “Radiation Oncology”.Methods561 patients, treated by Radiotherapy with curative intent between 2003 and 2012, were classified according to the five risk-classes of the Candiolo nomogram and the three risk-classes of the D’Amico classification for comparison. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The Candiolo nomogram appeared to be better and capable of predicting PC recurrence following a patient's radiotherapy than the traditional D'Amico risk classes [33]. An external validation study of this nomogram which was recently conducted also indicated that clinical use of Candiolo nomograms could be justified in PC patients prior to receiving radical radiotherapy [34].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The Candiolo nomogram appeared to be better and capable of predicting PC recurrence following a patient's radiotherapy than the traditional D'Amico risk classes [33]. An external validation study of this nomogram which was recently conducted also indicated that clinical use of Candiolo nomograms could be justified in PC patients prior to receiving radical radiotherapy [34].…”
Section: Discussionmentioning
confidence: 88%
“…D'Amico's risk classification first suggested a risk stratification system based on threegroups in order to predict a 2-year PSA failure rate following radical prostatectomy or EBRT. It categorizes patients into low, intermediate, and high risk groups based on their initial PSA, clinical stage, and biopsy GS [29,34]. In order to develop an algorithm to predict recurrence in PC patients treated with radical radiotherapy, Gabriele et al carried out a Candiolo nomogram that separated patients according to five risk groups that incorporated age, pretreatment PSA, clinical-radiological staging, GS, and the percentage of positive cores from the biopsy.…”
Section: Discussionmentioning
confidence: 99%